RESISTENSI REFORMASI PROCUREMENT : STUDI PENGADOPSIAN LPSE KEMENTERIAN KEHUTANAN - , FADHILAH FAJRIAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The most government agenda is to implement bureaucratic reform. Government activities that became spotlight which are full corrupt is government procurement. In the face of all the problems procurement, the government adopted an electronic procurement (e-procurement). Adoption of e-procurement as a form of reform of government procurement of goods and services is not without resistance from the bureaucracy itself. As it occurs at the Ministry of Forestry. The Ministry of Forestry has adopted the LPSE ever since 2012 . This research is to find why resistences occurs at the Ministry of Forestry and what are the factors inhibiting the resistences. Theoretical logic of this study is the adoption of e-procurement resistance. The resistance can be derived factors organizational, group and individual factors. Organizational factors can be either structural inertia, threat to the established power relations (conflict and power) and threats to resources. Factors that cause resistance group is the work group inertia and threats to resource allocation. Sedangka individual factors derived from threat to threat to expertise and resource allocation. Data was collected through direct observation, interviews, and secondary data collection. Interviews were conducted either in LPSE Ministry of Forestry, sub admin agency, committee procurement of goods and services, and providers of goods and services that a few times following the auction either electronically or manually at the Ministry of Forestry. The result is the resistance that occurs in the adoption of the Ministry of Forestry LPSE caused by resistance at the functional level due to conflicts and power factor . Besides that resistance is also caused by rent seeking actors procurement arise when it is applied to e-procurement, it will be difficult to deviate. Researchers recommend ( 1 ) institutional reforms, forming independent ULP LPSE and ( 2 ) to supervise the procurement of goods and services strictly ( 3 ) socialization of the importance of e-procurement ( 4 ) provision of reward and punishment to the agencies and officials who commit irregularities or who carry out the process of procurement of goods and services as well ( 5 ) greater commitment from policy makers related to the procurement of goods and services electronically. Keywords : Bureaucratic reform, resistance bureaucratic reform, e-procurement, LPSE